2019
DOI: 10.25124/jmi.v18i3.1731
|View full text |Cite
|
Sign up to set email alerts
|

Loyalitas Pasien Rumah Sakit Pemerintah: Ditinjau Dari Perspektif Kualitas Layanan, Citra, Nilai Dan Kepuasan

Abstract: Health development in Indonesia aims, among others, at making quality, fair and proportionate health services accessible to the Indonesian. Various development efforts have been implemented to realize such ideal covering infrastructure, medical personnel quality, access, health service process and professional attitude presented by hospital. This research objectively aims at analyzing patient loyalty from the perspectives of service quality, image, value and satisfaction of patients of hospitals in Makassar Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
33

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 18 publications
1
10
0
33
Order By: Relevance
“…The first thing to know is that to create legal protection for patients, and the parties must understand the rights and obligations attached to them, including health care providers, to be responsible for the profession provided to the recipients of health care services (Hasan & Putra, 2018). The law gives protection of the right to obtain health services for the community.…”
Section: Government Hospital Health Servicesmentioning
confidence: 99%
“…The first thing to know is that to create legal protection for patients, and the parties must understand the rights and obligations attached to them, including health care providers, to be responsible for the profession provided to the recipients of health care services (Hasan & Putra, 2018). The law gives protection of the right to obtain health services for the community.…”
Section: Government Hospital Health Servicesmentioning
confidence: 99%
“…100 triliun dengan jumlah pasien sebanyak 12.000 orang per tahun. 1 Hal ini diakibatkan karena tidak optimalnya kualitas layanan kesehatan didalam negeri (Indonesia), minimnya fasilitas kesehatan yang memadai, dan pelayanan yang kurang optimal, serta pasien menganggap tenaga kesehatan Indonesia seringkali salah dalam mendiagnosis. 2 Hal ini membuat banyak pasien yang berasal dari Indonesia berobat ke luar negeri salah satunya di Malaysia.…”
Section: Pendahuluanunclassified
“…Semakin baik kualitas pelayanan, maka citra rumah sakit akan semakin baik dan akan membuat pasien untuk kembali lagi menggunakan pelayanan jasa rumah sakit. Hasil ini didukung oleh beberapa penelitian sebelumnya 1,12,21 . Menurut Hasan et al 1 Citra yang baik dibangun dengan menjaga kepercayaan pasien dalam menyediakan layanan yang sempurna kepada pasien.…”
Section: Pengaruh Kualitas Pelayanan Terhadap Citra Rumah Sakitunclassified
“…Moreover, Gunawan and Saragih (2019) found that service quality and media service innovation are factors that influence the quality of service. According to Hasan and Putra (2018), the loyalty of a patient to a hospital service provider is influenced by the quality of service, image, value, and satisfaction.…”
Section: Introductionmentioning
confidence: 99%